Molecular cloning and characterization of Drosophila genes encoding small GTPases of the rab and rho families. - Sasamura, T.; Kobayashi, T.; Kojima, S.; Qadota, H.; Ohya, Y.; Masai, I.; Hotta, Y. (Molecular and General Genetics, 1997)
We have isolated eight genes from Drosophila, small GTPases. They can be classified into three rab family genes (Drab2, Drab5, Drab11) and five rho family genes (Drac1a, Drac1b, Drac3, Dcdc42, DrhoA). While Drac3 is a novel type of rac gene, others are homologues of known mammalian genes for small GTPases. Northern blot analyses showed that all the genes are expressed throughout all developmental stages from embryo to adult. In situ hybridization to embryos revealed that Drab2, Drac1b, and Drac3 are highly expressed in the nervous system, in the trunk mesoderm, and in the cephalic mesoderm, respectively. Since hemocytes are derived from the cephalic mesoderm, we carried out double stainings using a hemocyte marker anti-peroxidasin antibody and Drac3 in situ hybridization. We found that Drac3 is expressed in hemocyte precursor cells. In the Drac3 deficiency embryos, the hemocyte precursor cells start to differentiate normally, but never develop into mature hemocytes, indicating that Drac3 is essential for their maturation. The DrhoA and Dcdc42 genes complemented S. cerevisiae rho1 and cdc42 mutations in the same manner as human rhoA and CDC42, respectively. These results suggest functional similarity between Drosophila and mammalian small GTPase genes.